2014
DOI: 10.1073/pnas.1405739111
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic studies of polymerase η bypass of phenanthriplatin DNA damage

Abstract: Platinum drugs are a mainstay of anticancer chemotherapy. Nevertheless, tumors often display inherent or acquired resistance to platinum-based treatments, prompting the search for new compounds that do not exhibit cross-resistance with current therapies. Phenanthriplatin, cis-diamminephenanthridinechloroplatinum(II), is a potent monofunctional platinum complex that displays a spectrum of activity distinct from those of the clinically approved platinum drugs. Inhibition of RNA polymerases by phenanthriplatin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 30 publications
1
80
0
Order By: Relevance
“…These biochemical results were corroborated by an X-ray crystallographic study of pol η stalled at different stages of translesion synthesis. The structural data also confirmed that the orientational preference, observed in the small molecule studies described above [39], was preserved in the macromolecular structures and that the preferred diastereomer is the one responsible for arresting the polymerase [42].…”
Section: (B) Phenanthriplatin: a Potent Monofunctional Complexsupporting
confidence: 73%
“…These biochemical results were corroborated by an X-ray crystallographic study of pol η stalled at different stages of translesion synthesis. The structural data also confirmed that the orientational preference, observed in the small molecule studies described above [39], was preserved in the macromolecular structures and that the preferred diastereomer is the one responsible for arresting the polymerase [42].…”
Section: (B) Phenanthriplatin: a Potent Monofunctional Complexsupporting
confidence: 73%
“…Non-hydrolyzable nucleotide analogs such as dUMPNPP (dUTP*) and dAMPCPP have been shown to tightly bind the pol␤ active site (29,30), and the use of these analogs does not significantly alter the active site conformation of a pol␤ ternary complex (29,31). The dNTP* analogs have been used to obtain ternary complex structures of various DNA polymerases (17,32,34,35) including pol in complex with cisplatin-and phenanthriplatin-modified DNA (32,35). Unfortunately, our extensive efforts to crystalize a ternary complex of pol␤ incorporating dCTP* opposite the templating 3Ј-dG of the Pt-GG lesion failed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Arg-61 can adopt different conformations during each stage of the catalytic reaction cycle. In addition, the reported structures have also indicated that another highly conserved residue near the active site, Gln-38, may play an important role in stabilizing the template base in the nucleotidyl transfer reaction (10,11,21,30,34,35,37).…”
mentioning
confidence: 99%